Analysis of "green economy" phenomenon and tools of environment quality management: a case study for the Republic of Belarus - Rybak V. A., Grib A., Shokr A. (Interactive science, 2016)
the article carries out an analytical review of different approaches to defining the “green economy” phenomenon. The main fields and ways of using this term are described. The existing environmental management tools (environmental impact assessment, certification, auditing and the best available techniques) do not allow to evaluate environmental compatibility of projects and technologies, and are not able to specify the ways of their optimization. The authors suggest estimates of non-wastes, specific consumption, ecological and economical effectiveness, land capacity. The efficiency of reducing their values to a single integral component was proved in the article.
Keywords: управление качеством; энергоемкость; экологичность; зеленая экономика; экологическая экспертиза; безотходность; землеемкость; green economy; quality management; environmental impact assessment; environmental compatibility; non-wastes; specific consumption; land capacity